Canine idiopathic generalized tremor syndrome, immune-mediated? - Kajin, Filip; Meyerhoff, Nina; Meller, Sebastian; Carlson, Regina; Tipold, Andrea; Gutierrez-Quintana, Rodrigo; Kaczmarska, Adriana; Sanchez-Masian, Daniel; Ives, Edward; Brocal, Josep; von Klopmann, Thilo; Hauer, Julia; et al. (Frontiers in Veterinary Science, 2024)
Idiopathic generalized tremor syndrome is a disorder characterized by an acute onset of full-body tremors, sometimes accompanied by vestibulo-cerebellar signs, that is responsive to treatment with corticosteroids. Although considered to have an overall good outcome, relapsing and persistent mild clinical signs have been described. So far, little is known about the etiopathology of this syndrome, but it is believed to have an immune-mediated origin. In human medicine, description of numerous autoantibodies involved in certain non-infectious neurologic disorders has revolutionized understanding of their pathophysiology, diagnosis and treatment. In this multicenter retrospective study, we aimed to describe the clinical signs, course, and outcome of dogs with idiopathic generalized tremor syndrome and correlate potential findings with the presence or absence of autoantibodies associated with autoimmune cerebellar syndromes in humans. Information regarding signalment, history, clinical signs, laboratory findings, diagnostic imaging and testing for regional infectious diseases was gathered and the remaining serum and CSF samples were then analyzed for neural antibodies against targets associated with autoimmune encephalitic diseases of humans. Thirty-three dogs were included, and screening for neural antibodies was performed in 30 of those dogs. The analysis showed an increased titer of mGluR1 antibodies in two dogs, GFAP and later in the course of disease mGluR1 antibodies in one dog and an increase in unspecific autoantibodies which could not be further classified in two dogs. Dogs with detectable neural autoantibodies always had cerebrospinal fluid abnormalities in the form of a pleocytosis, with or without increased protein concentration, and tended to present with hyperthermia, potentially indicating a more severe clinical form of idiopathic generalized tremor syndrome in these cases. In conclusion, idiopathic generalized tremor syndrome is proposed to be an immune-mediated disorder potentially mediated by neural autoantibodies in a subgroup of dogs.